Relationship Between Baseline and Early Changes in C‐Reactive Protein and Interleukin‐6 Levels and Clinical Response to Tocilizumab in Rheumatoid Arthritis. Issue 6 (26th May 2016) - Wang, Jianmei; Devenport, Jenny; Low, Jason M.; Yu, Dale; Hitraya, Elena
Abstract : Objective: To clarify the relevance of measuring interleukin‐6 (IL‐6) and C‐reactive protein (CRP) levels in order to predict clinical response to tocilizumab (TCZ) in rheumatoid arthritis patients. Methods: In a pooled, post hoc analysis of 5 pivotal trials of TCZ, we examined the distributions of baseline serum concentrations of IL‐6 and CRP, stratified by randomized treatment group, and week 24 Disease Activity Score in 28 joints (DAS28) status (DAS28 <2.6 versus DAS28 ≥2.6). Relationships between early biomarker changes and later changes in DAS28 scores were evaluated using Spearman's correlations and scatterplots. Finally, percentage changes from baseline in IL‐6 and CRP levels were evaluated. Results: Distributions of baseline IL‐6 and CRP levels were similar for patients who achieved DAS28 scores <2.6 within 6 months of TCZ initiation and those who did not. Correlations between early changes in these 2 biomarkers and change in DAS28 scores were low (rho < 0.3 for all). Mean percentage increases from baseline in IL‐6 concentrations were observed in all treatment groups (highest in the 8 mg/kg dose group); mean percentage decreases in CRP concentrations were greater at week 2 and at all visits for the 8 mg/kg dose group. Conclusion: Baseline serum concentrations of IL‐6 and CRP may not be predictive of clinical outcomes after TCZ treatment. Data demonstrate the efficacy of TCZ in patients across a broad range of baseline serum IL‐6 and CRP concentrations. Similarly, changes in these biomarkers after TCZ dosing are expected and may or may not correspond to changes in other clinical signs and symptoms. These results complement previous reports describing the complex interactions among biomarker changes, other therapeutic mechanisms of action, and clinical outcomes.